Impact of Record Keeping on the Growth of Micro- and Small-scale Enterprises: An Analytical Study. Issue 2 (June 2019) - Khadim, Md Ekbal Hussain; Choudhury, Soma Roy Dey
It is well-recognised that micro and small enterprises (MSEs) are acting as specialist and soul of economic growth in India as well as in the world. MSEs are lifeblood of most economies and play a dominant role in the economic development of a country. Research on micro and small business development has shown that the rate of failure in developing countries is higher than in the developed world (Arinaitwe, 2006). The past studies indicate that three out of five businesses fail within the first few months of operation. A study by Peacock (1987) found that the lack of accounting records have led to the failure of these enterprises. This research study investigated the impact of record keeping on the growth of MSEs in the Cachar district of Assam. The objectives of the study were to analyse the relationship between record keeping practice and the growth of MSEs in the study area and to identify the status of record keeping in MSEs in the study area. To achieve these objectives, a sample of 93 entrepreneurs were selected from the targeted population. Primary data were collected by means of structured questionnaire. For data analysis, the study used descriptive statistics, and 'Pearson' correlation was used to establish the relationship between the dependent and independent variables. The finding of the study shows that there is a significance positive strong relationship between record keeping practice and growth of the MSEs in the study area.